NSCA's guide to high school strength and conditioning - McHenry, Patrick; Nitka, Mike; National Strength & Conditioning Association (U.S.).
"This book is a resource for strength and conditioning professionals and administrations in the high school environment. There will be a variety of components found in the book such as exercise descriptions, class lesson plans, curricula programming, coach and teacher checklists, and facility design and layout diagrams"--Provided by publisher.
CAC Camia (Recommending faculty) AY2022-2023
"National Strength & Conditioning Association."
Includes bibliographical references and index.
Keywords: Physical education and training -- Study and teaching (Secondary) -- United States; Muscle strength